Shear analysis of rice husk ash RHA reinforced tin- 0.7-copper composite solders on electroless nickel/immersion silver ENIAg surfaces - Mohamed Ariff, Azmah Hanim; Chuan, Khang Wei; Temitope T., Dele-Afolabi; Osman, Saliza Azlina (Wiley-VCH Verlag GmbH, 2021)
In this study, the mechanical performance of the rice husk ash-reinforced tin-0.7 copper composite solder was investigated. 0.01 wt.%, 0.05 wt.% and 0.1 wt.% of rice husk ash (RHA) were added to the solder matrix to prepare the composite solders. In order, to replace the costly electroless nickel immersion gold surface finish on the copper substrate, the effect of electroless nickel immersion silver (ENIAg) as the surface finish was studied. The differential scanning calorimetry (DSC) analysis showed that the composite solder exhibited lower melting temperature relative to the plain solder owing to the inclusion of rice husk ash. Shear strength analysis was carried out to investigate the influence of rice husk ash and electroless nickel immersion silver surface finish on the shear strength of the developed composite solders. The results proved that the rice husk ash failed to enhance the shear strength of tin-0.7 copper lead-free solder with the plain solder exhibiting the highest shear strength.